The Demand Driven MRP Implementation in Complex Manufacturing Industries: A Systematic Literature Reviews - Benavente, Daniel (2023)
Since its creation in 2011, the DDMRP planning method has been catalogued as an important tool to deal with the high variability of the environment, especially in demand, since it allows modifying inventory levels without neglecting the level of service and quality of the products. However, the volume of research available on this method is small, even more, so those considering the application in complex industries. The objective of this research was to analyze the available literature about the application of the model in complex industries, considering its application trends, buffer positioning and improvement target factors. In addition, it allowed identifying areas that other researchers should study in the future. This systematic review scrutinized different applications of the method in complex industries worldwide by analysing literature in different languages. This research identified that certain characteristics of the DDMRP require further study, especially real and simulated applications. On the one hand, more research is required in applying the last two phases of the method (planning based on demand and visible and collaborative execution), as well as the need to deepen in economic terms and the possibility of combining it with other similar or complementary methods. Thanks to this literature review, it was possible to recognize the impact of the implementation of the DDMRP in complex industries, identify the factors that influence its effectiveness and describe the need to delve into various issues that have not yet been analyzed in depth, seeking to understand the best way the studied method.